Clinical characteristics of meconium aspiration syndrome in neonates with different gestational ages and the risk factors for neurological injury and death: A 9-year cohort study - Luo, Lei; Zhang, Meng; Tang, Jun; Li, Wenxing; He, Yang; Qu, Yi; Mu, Dezhi (Frontiers in Pediatrics, 2023)
Background: The presence of meconium is associated with gestational age, and the incidence of meconium aspiration syndrome (MAS) increases with gestational age. Our study compared the differences in the clinical characteristics of patients with MAS at different gestational ages and discussed the risk factors for neurological injury and death from MAS. Methods: A total of 294 neonates diagnosed with MAS between 2013 and 2021 were included. Patients were divided into preterm, early-term, full-term, and late-term groups according to gestational age. We compared the patients' basic demographic, treatment, complications, and clinical outcomes in the different groups. We also analyzed the risk factors of neurological injury and death in patients with MAS. Results: The mean age at admission (0.55 ± 0.9 h) was lower and the proportion of cesarean deliveries (90.00%, 27/30) was higher in the preterm group than in the other three groups. There was no statistically significant difference among the four groups regarding 1- and 5-min Apgar scores and the need for delivery room resuscitation. In terms of complications, early-term infants had the highest incidence of neurological injury (52.9%, 27/51), and late-term infants had the highest incidence of pneumothorax (37.8%, 17/45). The overall mortality rate of children with MAS was 7.80% (23/294), and the difference in mortality rates among the four groups was not significant. Low 1-min Apgar score and gestational age, metabolic acidosis, and respiratory failure were independent risk factors for neurological injury; metabolic acidosis, respiratory failure, and sepsis were independent risk factors for death in neonates with MAS. Conclusion: The clinical characteristics of MAS neonates of different gestational age are different mainly in complications. Early-term infants are more likely to complicate with neurological injury, and late-term infants are more likely to complicate with pneumothorax. Low 1-min Apgar score and gestational age, metabolic acidosis, and respiratory failure were established as risk factors for neurological injury; metabolic acidosis, respiratory failure, and sepsis were independent risk factors for death in neonates with MAS.